(untitled) (Annals of Medical Research, 2021)
Aim: While 90-95% of the adult population responds to hepatitis-B vaccination, it is known that, this rate is lower in patients with CD. In our study, determination of response rates of vaccinated celiac patients, and the affecting factors associated with vaccine responses were the aims of our investigation. Material and Methods: The study included 280 celiac patients who applied to the polyclinic between 2015-2019 years. Demographic, anthropometric characteristics (age, gender, onset age, disease duration, smoking, body mass index(BMI), waist-hip ratios) and symptoms in patients were documented. Hepatitis B, C, delta serology were examined. The prevalence of chronic hepatitis and associated risk factors were evaluated. Hepatitis-B vaccination rates and vaccine responses were determined. The risk factors associated with the immune response were reviewed. Results: 212 (75.7%) of the patients were female, the mean-age of the patients was 33.4±10.8 and the disease duration was 4.9±3.7 years. In 14 (5%) of the patients there were chronic viral infections, 18 (6.4%) had natural immunity, 92 (32.9%) were immunized, 58 (56.4%) were not encountered with viral infection. No significant correlation was found between the presence of chronic viral hepatitis and risk factors. 28 (30.4%) patients who had not vaccine response. It was observed that; the dietary incompatibility and absence of immunological remission were significantly higher, the BMI and the waist size were significantly lower in non-response group (P0.05). Conclusions: Considering the mild-high prevalence of chronic viral infection in celiac patients, it is important to vaccinate these patients against infections. It is of great importance to implement re-vaccination protocol in the patients without vaccine response.Keywords: Celiac disease; hepatitis B; vaccination.